Hotspot or blind spot? Historical perspectives on surveillance and response to epidemics in the Central African Republic - (:unkn) unknown (My University, 2020)
PMD wants to thank Guillaume Lachenal for his support. We want to thank Dominique Dupenne and Daniel Demellier for their help at the Department of Archives at the Pasteur Institute in Paris. We are also very grateful to Jean-Pierre Lombart for his welcome at the Institut Pasteur de Bangui.
Keywords: African Research